2020
DOI: 10.1055/s-0040-1716894
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Partial Splenectomy Assisted by Fluorescence in a 13-Year-Old Girl

Abstract: Partial splenectomy allows preserving immune function in benign splenic lesions such as epidermoid cysts. Determining the plane of resection and perfusion of the spleen remnant can be difficult, especially in centrally located lesions. We present a 13-year-old girl with a symptomatic splenic cyst of 6 cm in diameter located next to the splenic hilum. Laparoscopic partial splenectomy was performed through a 10-mm umbilical approach and three accessory 5-mm ports. Intraoperative intravenous injection of indocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Additionally, several papers explored the application of fluorescence in non-neoplastic lesions: one case of lung lesion resection entailed granulomatous inflammation with focal necrosis [ 47 ], one case of laparoscopic resection of a pancreatic nodule entailed a case of focal congenital hyperinsulinism [ 48 ], and one case of laparoscopic partial splenectomy entailed a splenic cyst [ 49 ]. Additionally, there was one case of thoracoscopic cystic adenomatoid malformation resection and one case of thoracoscopic pulmonary extra-lobar sequestration resection [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several papers explored the application of fluorescence in non-neoplastic lesions: one case of lung lesion resection entailed granulomatous inflammation with focal necrosis [ 47 ], one case of laparoscopic resection of a pancreatic nodule entailed a case of focal congenital hyperinsulinism [ 48 ], and one case of laparoscopic partial splenectomy entailed a splenic cyst [ 49 ]. Additionally, there was one case of thoracoscopic cystic adenomatoid malformation resection and one case of thoracoscopic pulmonary extra-lobar sequestration resection [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that routine use of ICG would be indicated in straightforward cases. However, it could be useful in the identification and division of the splenic artery and vein in cases where there is anatomic distortion or adhesions from prior inflammation[ 79 ]. This is important as bleeding from these vessels can be substantial, and it is more difficult to obtain control in laparoscopic or robotic surgery compared to open surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Bertolucci et al [ 81 ] reported a case where ICG was used in a laparoscopic splenic artery aneurysmectomy to confirm successful clip and resection of aneurysm. The use of ICG FI also enabled assessment of splenic blood supply, allowing for laparoscopic partial splenectomy in 4 patients[ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ours is the first report to describe the use of ICG fluorescence in surgery for splenic cysts. Bada‐Bosch et al 10 reported the performance of pediatric partial splenectomy for splenic cysts using ICG fluorescence for guidance. They used ICG and confirmed the transection line of the spleen after ligature of splenic vessels.…”
Section: Discussionmentioning
confidence: 99%